2020
DOI: 10.3390/jcm9041229
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anesthesia and Clinical Variables on the Firing Rate, Coefficient of Variation and Multi-Unit Activity of the Subthalamic Nucleus in Patients with Parkinson’s Disease

Abstract: Background: Microelectrode recordings (MER) are used to optimize lead placement during subthalamic nucleus deep brain stimulation (STN-DBS). To obtain reliable MER, surgery is usually performed while patients are awake. Procedural sedation and analgesia (PSA) is often desirable to improve patient comfort, anxiolysis and pain relief. The effect of these agents on MER are largely unknown. The objective of this study was to determine the effects of commonly used PSA agents, dexmedetomidine, clonidine and remifent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…Many centers employing MER-based DBS surgery prefer to perform the procedure under awake conditions to obtain reliable neurophysiological mapping and enable intraoperative test stimulation to observe the motor improvement and potential side-effects. In our recent work we have shown that anesthetic agents alter the firing characteristics of the STN, which is consistent with data obtained from previous studies [ 10 , 11 , 12 , 13 , 14 , 15 ]. These findings provide important arguments to avoid the use of anesthetic drugs during DBS surgery.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…Many centers employing MER-based DBS surgery prefer to perform the procedure under awake conditions to obtain reliable neurophysiological mapping and enable intraoperative test stimulation to observe the motor improvement and potential side-effects. In our recent work we have shown that anesthetic agents alter the firing characteristics of the STN, which is consistent with data obtained from previous studies [ 10 , 11 , 12 , 13 , 14 , 15 ]. These findings provide important arguments to avoid the use of anesthetic drugs during DBS surgery.…”
Section: Introductionsupporting
confidence: 92%
“…Dexmedetomidine and clonidine produce dose-dependent sedation, analgesia, and anxiolysis [ 33 , 34 ]. Contrary to most sedatives, α 2 agonists do not have a direct gamma-aminobutyric acid (GABA)-ergic effect and so have a less profound effect on MER compared to the GABA-ergic drugs [ 10 , 32 ]. Remifentanil, acting mainly on the mu opioid receptor agonist, has limited effects on STN neuronal activity at low doses, though a recently published report showed a significant reduction in STN neuronal activity with doses above 0.1 µg/kg/min [ 10 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their literature review forms the basis to initiate non-inferiority studies to confirm the safety and efficacy of DBS surgeries under general anesthesia. In our electrophysiology study, we studied the effects of procedural sedation and analgesia (PSA) on MER [ 9 ]. One of our main findings was that dexmedetomidine reduces the power of the multi-unit activity (MUA) in a dose-dependent matter.…”
mentioning
confidence: 99%